Butylidenephthalide facilitates contractions via nonspecific binding to receptors in isolated guinea-pig vas deferens. (1st January 2019) - Shih, Chung-Hung; Chen, Chi-Ming; Ko, Wun-Chang
Abstract: Context: Butylidenephthalide (Bdph) has been reported to inhibit rat uterine contractions, but significantly potentiate the noradrenaline (NA)-induced contractions in guinea-pig vas deferens (GPVDs). Objective: The present study elucidates the binding specificity of Bdph in GPVD to potentiate contractions. Materials and methods: Electrical field stimulation (EFS, supramaximal voltage, 1 ms and 1 Hz) or exogenous NA (50 μM) was applied to the GPVD in Krebs or 1/10 Mg-Tyrode's solution, respectively. After the clonidine (10 nM)-induced twitch inhibition or the exogenous NA-induced contractions reached a constant, Bdph (50 µM) was added 2 min prior to the subsequent addition of NA (50 µM). Three experiments were performed. In the presence of Bdph (100 μM), the release of NA in the medium and remaining NA content in the tissues were determined after EFS-stimulation. Results: Bdph (100 μM) significantly antagonized the clonidine (10 nM)-induced twitch inhibition from 22.5 ± 2.1 to –11.4 ± 1.6% ( n = 6) and dibutyryl-cAMP (300 μM) from 25.7 ± 3.2 to 7.9 ± 4.0% ( n = 8). Bdph (100 μM) significantly increased the electrically stimulated release of NA from 393.0 ± 109.5 to 1000.0 ± 219.1 ng/g ( n = 6). Bdph (50 μM) potentiated the exogenous NA (50 μM)-induced contractions from 3.0 ± 0.06 to 3.9 ± 0.06 g ( n = 3), but after washout of Bdph, the response to NA gradually curtailed. Discussion and conclusions: Bdph action may be through the nonspecific binding of the butylidene group to prejunctional α2 - and postjunctional α1 -adrenoceptors to reversibly block K + channels, and irreversibly block VDCCs on the smooth muscle cell membrane, respectively.